COVID 19 IN CHILDREN: AN EXPERIENCE FROM A PAEDIATRIC TERTIARY CARE SETTING - Bibi, Saima; Gilani, Syed Yasir Hussain; Abbas, Zaheer; Bibi, Sadia; Adil, Farrukh; Siddiqui, Tahir Saeed (Journal of Ayub Medical College Abbottabad, 2021)
Background: The pandemic of COVID 19 has affected a number of people around the globe. The data from paediatric population is scarce. The present study is aimed to present the paediatric perspective of the disease in terms of different clinical presentations, laboratory parameters, complications, and outcomes so as to develop an insight into disease manifestations in children. Methods: This descriptive case series was conducted in the department of Paediatrics after approval of institutional review board. All children admitted in paediatric unit with confirmed SARS-COV-2 infection either by PCR or antibody test were included in the study. Patients' characteristics were documented on a predesigned proforma and analysed using SPSS 26.0. Results: A total of 17 patients comprising 13 (76.5%) male and 4(23.5%) female were included in the study. The major clinical features were fever, cough and shortness of breath documented in 15 (88.2 %) patients. Major complications were shock in 13 (76.5%), respiratory complications in 16 (94.11%), CNS complications in 4 (23.5%), cardiac complications in 5 (29.4%), hepatic involvement in 3 (17.6%) Acute Kidney Injury in 4 (23.5%) patients and 9 (52.9 %) patients were labelled as having Multisystem Inflammatory Syndrome in Children (MIS-C). A total of 7 (41.2%) patients had coexistent comorbid diseases. A total of 13 (76.47%) patients were discharged, 2 (11.8%) patients expired and 2 (11.8%) left against medical advice. Conclusion: The clinical presentation of paediatric patients with SARS-COV-2 infection is highly variable. Multisystem inflammatory syndrome associated with SARS-COV-2 must be considered in the differential diagnosis of children presenting with multiorgan dysfunction.